Virtual, augmented and mixed reality : 11th International Conference, VAMR 2019, held as part of the 21st HCI International Conference, HCII 2019 Orlando, FL, USA, July 26-31, 2019, proceedings, Part I /: 11th International Conference, VAMR 2019, held as part of the 21st HCI International Conference, HCII 2019 Orlando, FL, USA, July 26-31, 2019, proceedings, Part I. ([2019]) - Unknown
No abstract available